Gezi Park analysis as an example of social movement - Mutlu, Sercan (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This article aims to analyze the Gezi Park social movement, which started in Istanbul in 2013 and spread all over Turkey in a short time, in the context of class dynamics. In this context, firstly, the adequacy of examining the Gezi Park movement within the scope of new social movements will be emphasized. Secondly, the study will attempt to establish an alternative critical approach based on class. With this approach, class dynamics of the Gezi Park movement will be sought under the titles of historicity, antagonism, and holism.
Keywords: Gezi Park; social movements; new social movements; social classes; class struggle